Pattern of stress-strain accumulation due to a long dip-slip fault movement in a viscoelastic layered model of the lithosphere - asthenosphere system - Debnath, Subrata K.; Sen, Sanjay (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a modeling method and mathematical description of a two-wheeled self-balancing vehicle and its rider. A model of the rider that was used contains a model of the ankle joint, so we could determine the interaction between the rider and the vehicle. The paper presents results of computer simulations, which show the fundamental processes during riding, such as acceleration and braking.
Keywords: aseismic period; dip-slip fault; earthquake prediction; stress accumulation; viscoelastic-layered model